Improving Learning Motivation in Islamic Education Through Animation Video Media - Putri Nurul Fadillah; Imam Tabroni; Nur Aisah Jamil (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to compare the effectiveness of animated video media and without animated video media in increasing student motivation in Islamic Religious Education and Moral Education subjects. The research method used is quantitative using true experimental, with pretest-posttest control group design. Respondents were UPTD students at SDN 2 Nagrikidul. The results showed that animated video media was more effective than no animated video media in increasing students' motivation to study Islamic Religious Education and Moral Character with an average result of 0.028, and student learning motivation increased with an average result of 0.000, less than 0. 05. Student motivation is influenced by extrinsic motivation, learning motivation increases after students are given treatment with animated video media